Finite element modelling of reinforced masonry walls under axial compression. (1st February 2022) - Asad, Mohammad; Zahra, Tatheer; Thamboo, Julian; Song, Mengli
Highlights: Segmental modelling technique was created to analyse RM walls under compression. Arc-length algorithm was used to account the axial buckling effects of the walls. The developed modelling technique was verified against the experimental data. The behaviour of slender RM walls were analysed and compared against the design provisions. Abstract: This paper presents the development of 3D finite element (FE) technique to model and analyse reinforced masonry (RM) walls under axial compression. The Arc-length algorithm integrated with initial geometric imperfection has been used to model the geometric nonlinear response of both the embedded steel and that of the RM wall to allow for the occurrence of buckling under concentric compression. A segmental modelling technique was developed to consider geometric and material nonlinearities of each component of a RM wall such as block, mortar, grout and reinforcement bars. The modelling parameters were calibrated using the RM wall experimental testing program previously conducted by the authors in which three series of RM walls with different slenderness ratios (4, 7 and 12) were tested under axial compression. The applicability of the models was verified using the experimental data in terms of axial load-deflection responses and strain in vertical steel bars. It was determined that the developed modelling technique was able to capture the experimental responses with reasonable accuracy. Further, the verified FE model was used to predict the responses of RM walls of higher slenderness ratios (21, 26, 32 and 42) to examine the probable buckling of taller RM walls. The failure modes and the ultimate capacity of slender RM walls have been reported and the potential of using the RM for taller walls are discussed against the existing code provisions.